Government Policies on Raising Cigarette Taxes and Excise for Indonesians According to Tasharruful Imam Ala Ra'iyyah Manuthun Bil Maslahah Rules - M. Ridza Muzkira; Hasanuddin Yusuf Adan (Teunuleh Publisher, 2026)
This study examines the Indonesian government's policy of increasing tobacco excise rates from the perspective of fiqh siyasah, specifically the principle of Tasharruful Imam 'Ala Ra'iyah Manuthun BilMaslahah, which asserts that every action of a leader must be oriented toward public welfare. The main focus of this research is to analyze the effectiveness of the exercise policy in reducing cigarette consumption, minimizing health impacts, and increasing state revenue amid the growing circulation of illegal cigarettes. This study employs a normative legal method with a juridical-normative approach through library research that reviews relevant regulations, academic literature, and data from official institutions. The findings indicate that, normatively, the policy has a strong legal foundation, namely Law Number 39 of 2007 concerning Excise and Government Regulation Number 28 of 2024 concerning the Control of Addictive Substances. Theoretically, this policy is effective through the mechanism of price elasticity; however, in practice, its effectiveness is hindered by the widespread distribution of illegal cigarettes, weak enforcement, complex tax structures, and low public awareness. Therefore, optimizing the tobacco excise policy requires simplifying the excise structure, strengthening law enforcement against illegal cigarettes, and implementing cross-sectoral educational campaigns grounded in Islamic ethics and social justice. Through these comprehensive measures, the excise policy can function not only as a fiscal instrument but also as a tangible manifestation of public health protection and societal welfare.